2021
DOI: 10.1111/jog.14930
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of psychosocial dimensions associated with postpartum depression

Abstract: Aim: The aim of the study was psychometric properties of a questionnaire for assessing psychosocial dimensions associated with postpartum depression (PAPP). Methods: Initial form of the questionnaire for assessing PAPP was developed based on the results of a qualitative study. Principal component analysis was used to determine the construct validity, as well as Cronbach's alpha and intraclass correlation coefficient to determine the reliability of the questionnaire. Construct validity, predictability of the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
1
10
0
2
Order By: Relevance
“…36 37 Additionally, although all postpartum women are vulnerable to changes in sleep quality, it was found that the chances of sleep disorders were 1.77 times greater at the age extremes (under 18 years old and over 35-years-old). This can be explained by the high prevalence of high-risk pregnancies and, consequently, complications in childbirth, 38 greater social vulnerability, lack of partner support (mainly observed in very young women), 39 and teenage pregnancy. 13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 37 Additionally, although all postpartum women are vulnerable to changes in sleep quality, it was found that the chances of sleep disorders were 1.77 times greater at the age extremes (under 18 years old and over 35-years-old). This can be explained by the high prevalence of high-risk pregnancies and, consequently, complications in childbirth, 38 greater social vulnerability, lack of partner support (mainly observed in very young women), 39 and teenage pregnancy. 13…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reinforced that the absence of social support is associated with poor sleep quality in the postpartum period. 13 39…”
Section: Discussionmentioning
confidence: 99%
“…The demographic profile of our study population revealed several noteworthy trends. While the mean age of participants was 28.5 years, a diverse age range was observed, highlighting the relevance of studying postpartum mental health across various life stages (Ghaedrahmati et al, 2017;Lubotzky-Gete et al, 2021;Rollè et al, 2017;Shorey et al, 2018). Most participants were married, and a significant proportion had obtained at least a high school education, emphasizing the importance of considering both marital status and educational background as potential factors influencing mental health outcomes (Vismara et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Postpartum PTSD refers to a stress-induced mental disorder that occurs in the perinatal period due to exposure to childhood abuse, perinatal complications, traumatic childbirth, or the delivery of high-risk neonates. 4 According to the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-V) in 2013, 5 the main symptoms of postpartum PTSD include intrusion or re-experiencing the traumatic event, avoidance of anything related to the traumatic event, negative alterations in cognitions and mood, arousal, and reactivity. 6,7 Giving birth is a major life event and results in significant physical and psychological changes for women.…”
Section: Introductionmentioning
confidence: 99%